Rancang Bangun Prototype Jemuran Pakaian Otomatis Berbasis Internet Of Things (Iot) Dengan Raindrop Sensor Dan Sensor Light Dependent Resistor (Ldr)Di Leon Laundry - Dayan Singasatia; Andri Setiawan; M. Imam Sulistyo; Bintang Yudhistira (Jurnal Teknologika, 2025)
Unpredictable weather often complicates the process of drying clothes, especially when rain suddenly falls. This becomes a challenge for both households and laundry businesses. This research aims to design an automatic clothes drying system based on the Internet of Things (IoT), utilizing a rain sensor and a light sensor to detect weather conditions in real-time and automatically adjust the position of the drying rack. The research uses the prototype method, which includes rapid design, device construction, and system testing. The device is controlled by a NodeMCU ESP8266 and connected to the Blynk application for remote monitoring. A BYJ-48 stepper motor moves the drying rack based on input from the rain sensor and LDR (Light Dependent Resistor). Test results show that the system works well and responds quickly to weather changes. The drying rack automatically retracts during rain or low light conditions and extends when the weather is clear. This system offers convenience, efficiency, and a practical solution for everyday clothes drying activities